A comparative study of nebulized 3% hypertonic saline and normal saline in the management of respiratory syncytial virus-positive acute bronchiolitis in young infants - Khanom, Mahmuda; Sarkar, Probir Kumar; Sayeed, K. M. Ishtiaque; Amin, M. Mahbub Al; Ferdous, Fahmida; Tonny, Ayesha Siddika; Bhuiyan, Farhana (International Journal of Contemporary Pediatrics, 2025)
Background: Acute bronchiolitis due to respiratory syncytial virus (RSV) is a major cause of hospitalization in infants, yet optimal therapeutic strategies are still under evaluation. Hypertonic saline has gained interest for its potential mucolytic and anti-edematous benefits. This study aimed to evaluate the clinical efficacy of nebulized 3% hypertonic saline compared to 0.9% normal saline in managing RSV-positive acute bronchiolitis in infants up to two months old. Methods: A double-blind, randomized controlled trial was conducted at Dhaka Shishu (Children) hospital involving 90 infants aged≤60 days with confirmed RSV-positive bronchiolitis. Participants were randomly assigned to receive either nebulized 3% hypertonic saline or 0.9% normal saline, administered three times daily until discharge. Clinical efficacy was measured using the modified respiratory distress assessment instrument (MRDAI), duration of oxygen therapy, and length of hospital stay. Results: The hypertonic saline group showed significantly greater clinical improvement starting at 12 hours post-intervention (MRDAI: 5.20±0.19 vs. 5.98±0.23; p=0.005). These infants also required shorter oxygen therapy (10.12±1.61 vs. 11.54±1.46 hours; p=0.025) and had significantly reduced hospital stays (62.98±2.29 vs. 79.64±3.69 hours; p=0.0001). Conclusions: Nebulized 3% hypertonic saline is more effective than normal saline in improving clinical outcomes in RSV-positive bronchiolitis in infants under two months, significantly reducing disease severity, oxygen requirement, and hospitalization duration. Incorporation into treatment protocols is strongly recommended.